Implementation of Gamification in Data Processing with Statistical Visualization for using Google Cloud for Monitoring Performance and Improvement Evaluation of Personnel at PT. Surveyor Indonesia - Fajri Arvandi; Pariyadi (Yayasan Kita Menulis, 2025)
Efficient data management is a crucial requirement for large companies like PT. Surveyor Indonesia to enhance performance and make strategic decisions. This research aims to develop an interactive web-based system with a gamification concept, utilizing technologies such as Laravel, MySQL, and Google Cloud Compute Engine. The system is designed to visualize personnel performance data, provide statistical information, and motivate employees through the implementation of a leveling and points system. By leveraging Google Cloud, the developed system is capable of offering high scalability, flexibility, and ease of access. This research is expected to significantly contribute to the operational data management at PT. Surveyor Indonesia and serve as a model for implementing similar systems for other needs.